Efeito subletal do fipronil sobre o sistema hepatonefrocítico de Bombus atratus (Swederus, 1787) (Hymenoptera Bombini). - Nogueira, Felipe Lissoni de Andrade (Universidade Federal de São Carlos, 2025)
Pollination by native bee species of the genus Bombus is essential for ensuring the sexual reproduction of plants and human food security. However, these bees are experiencing population decline due to several factors, including exposure to sublethal doses of pesticides. Fipronil is an agrochemical with inhibitory action on neuronal postsynaptic receptors, causing excessive stimulation of neurons in the insect's nervous system. The study found that sublethal concentrations of fipronil found in the field and used in agricultural systems could harm the organism of Bombus atratus. Therefore, the study analyzed the effects of sublethal concentrations of fipronil (1.5 μL L-1, 2.5 μL L-1, and 3.5 μL L-1) on the cells of the hepatonephrocytic system (HNS) of B. atratus, using biomarkers. Therefore, morphological, morphometric, genotoxic, fluorescence histochemical, and histochemical analyses of trophocytes, oenocytes, and pericardial cells were performed. The results indicated that the analyzed fipronil concentrations damaged the analyzed cell groups of the SHN of B. atratus, with milder effects in the treatment of 1.5 μL L-1and accentuated exposures to 2.5 μL L-1 and 3.5 μL L-1. Exposures to 2.5 μL L-1 and 3.5 μL L-1 caused damage of similar intensity to the SHN cells of B. atratus. Morphological analysis of the trophocytes indicated loss of the branched nuclear shape at all analyzed concentrations, while exposures to 2.5 μL L-1 and 3.5 μL L-1 caused cytoplasmic vacuolization and chromatin compaction. Oenocytes showed chromatin compaction at all concentrations analyzed. Pericardial cells showed cytoplasmic vacuolation, were observed in stages II and III of activation, and showed chromatin compaction at all concentrations analyzed. Morphometric analysis indicated a decrease in the cell area of trophocytes and oenocytes in the groups exposed to 2.5 μL L-1 and 3.5 μL L-1 (P < 0.0001), while pericardial cells showed an increase in cell area at all exposures analyzed (P < 0.0001) due to pinocytic activity of the hemolymph and vacuolation of the cytoplasm. Genotoxic analysis indicated that all concentrations analyzed damaged the genetic material of the cells, with greater intensity in relation to exposures to 2.5 μL L-1 and 3.5 μL L-1 (P < 0.0001). Fluorescence histochemical analysis indicated that exposure to 2.5 μL L-1 and 3.5 μL L-1 caused chromatin fragmentation in all cell groups analyzed, as indicated by the observed red nuclei. Histochemical analyses indicated that protein content decreased in trophocytes and pericardial cells, while remaining unchanged in oenocytes, at all concentrations analyzed. Glycogen and triglyceride contents remained unchanged in all treatments and cell groups analyzed. The results indicated that fipronil's action impaired the mobilization of molecules, impairing the energy metabolism of bees in the exposed groups. The study concluded that the effects of sublethal fipronil concentrations found in the field harmed HNS cells and the B. atratus organism.
Sublethal effect of fipronil on the hepatonephrocytic system of Bombus atratus (Swederus, 1787) (Hymenoptera Bombini).
Keywords: Ecotoxicologia; Agrotóxicos; Biomarcadores; Abelhas Nativas Brasileiras; Ecotoxicology; Pesticides; Biomarkers; Brazilian Native Bees; CIENCIAS BIOLOGICAS::MORFOLOGIA::CITOLOGIA E BIOLOGIA CELULAR; CIENCIAS BIOLOGICAS::MORFOLOGIA::HISTOLOGIA